Impairment of Bone Remodeling in LIGHT/TNFSF14‐Deficient Mice. (11th December 2017) - Brunetti, Giacomina; Faienza, Maria Felicia; Colaianni, Graziana; Gigante, Isabella; Oranger, Angela; Pignataro, Paolo; Ingravallo, Giuseppe; Di Benedetto, Adriana; Bortolotti, Sara; Di Comite, Mariasevera; Storlino, Giuseppina; Lippo, Luciana; et al.
ABSTRACT: Multiple cytokines produced by immune cells induce remodeling and aid in maintaining bone homeostasis through differentiation of bone‐forming osteoblasts and bone‐resorbing osteoclasts. Here, we investigate bone remodeling controlled by the tumor necrosis factor (TNF) superfamily cytokine LIGHT. LIGHT ‐deficient mice ( Tnfsf14 ‐/‐ ) exhibit spine deformity and reduced femoral cancellous bone mass associated with an increase in the osteoclast number and a slight decrease of osteoblasts compared with WT mice. The effect of LIGHT in bone cells can be direct or indirect, mediated by both the low expression of the anti‐osteoclastogenic osteoprotegerin (OPG) in B and T cells and reduced levels of the pro‐osteoblastogenic Wnt10b in CD8 + T cells in Tnfsf14 ‐/‐ mice. LIGHT stimulation increases OPG levels in B, CD8 + T, and osteoblastic cells, as well as Wnt10b expression in CD8 + T cells. The high bone mass in Light and T‐ and B‐cell‐deficient mice ( Rag ‐ /Tnfsf14 ‐ ) supports the cooperative role of the immune system in bone homeostasis. These results implicate LIGHT as a potential target in bone disease. © 2017 American Society for Bone and Mineral Research.